Ambiguous Citizenship in an Age of Global Migration. - Ní Mhurchú, Aoileann (Edinburgh University Press, 2014)
Many people see citizenship in a globalised world in terms of binaries: inclusion/exclusion, past/present, particularism/universalism. Aoileann Ní Mhurchú points out the limitations of these positions and argues that we need to be able to take into account the people who get caught between these traditional categories. Using critical resources found in poststructural, psychoanalytic and postcolonial thought, Ní Mhurchú thinks in new ways about citizenship, drawing on a range of thinkers including Kristeva, Bhabha and Foucault. Taking a distinctive theoretical approach, she shows how citizenship is being reconfigured beyond these categories.